2018
DOI: 10.7150/thno.26345
|View full text |Cite
|
Sign up to set email alerts
|

Imaging and therapy of ovarian cancer: clinical application of nanoparticles and future perspectives

Abstract: Despite significant advances in cancer diagnostics and treatment, ovarian cancers (OC) continue to kill more than 150,000 women every year worldwide. Due to the relatively asymptomatic nature and the advanced stage of the disease at the time of diagnosis, OC is the most lethal gynecologic malignancy. The current treatment for advanced OC relies on the synergistic effect of combining surgical cytoreduction and chemotherapy; however, beside the fact that chemotherapy resistance is a major challenge in OC managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 128 publications
0
39
0
Order By: Relevance
“…Compared to other photosensitizers, this new PS has the capacity to induce higher cellular death 24 h after illumination [28]. Furthermore, most of the FR-targeted PS are coupled with nanoparticles; however, previous observations have suggested that the application of NPs for intra-peritoneal delivery is limited by their rapid clearance from the peritoneal cavity due to lymphatic drainage [29]. Therefore, we bypassed this problem with a folate chemically coupled PS.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to other photosensitizers, this new PS has the capacity to induce higher cellular death 24 h after illumination [28]. Furthermore, most of the FR-targeted PS are coupled with nanoparticles; however, previous observations have suggested that the application of NPs for intra-peritoneal delivery is limited by their rapid clearance from the peritoneal cavity due to lymphatic drainage [29]. Therefore, we bypassed this problem with a folate chemically coupled PS.…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian cancer (OC) continues to kill more than 150,000 women every year worldwide 1 . It is usually advanced when diagnosed.…”
Section: Introductionmentioning
confidence: 99%
“…The intraperitoneal (IP) cavity is the principal site of OC disease [102]. Metastatic OC cells accountable for high mortality rate disseminate and recur at the intraperitoneal site [103]. Hence, IP nanomicellar chemotherapy is the favorable route of administration of OC treatment, with improved patient compliance as compared to intravenous (IV) treatment [104][105][106].…”
Section: Treatment Of Ovarian Cancer Using Nanomicellesmentioning
confidence: 99%